ZBTB20 Positively Regulates Oxidative Stress, Mitochondrial Fission, and Inflammatory Responses of ox-LDL-Induced Macrophages in Atherosclerosis. (11th March 2021) - Tao, Jun; Qiu, Junxiong; Lu, Liuyi; Zhang, Lisui; Fu, Yuan; Wang, Meng; Han, Jingjun; Shi, Maomao; Li, Ling; Zhao, Zongkai; Wei, Feng; Wang, Chao; et al.
Abstract : Atherosclerosis (AS) is one of the most serious and common cardiovascular diseases affecting human health. AS is featured by the accumulation of plaques in vessel walls. The pathophysiology of AS is relevant in the low-density lipoprotein (LDL) uptake by macrophages, as well as the conversion of macrophages to foam cells. However, the mechanisms about how macrophages regulate AS have not been fully elucidated. In this study, we aimed to illuminate the roles of ZBTB20 and to excavate the underlying regulative mechanisms of ZBTB20 in AS. The microarray analysis revealed that ZBTB20 was a hub gene in the oxidative stress and inflammatory responses induced by oxidized LDL (ox-LDL) in AS. Correspondingly, our validation studies showed that ZBTB20 increased in either the human atherosclerotic lesion or the ox-LDL-stimulated macrophages. Moreover, the knockdown of ZBTB20 decreased M1 polarization, suppressed the proinflammatory factors, inhibited mitochondrial fission, and reduced the oxidative stress level of macrophages induced by ox-LDL. The mechanistic studies revealed that the ZBTB20 knockdown suppressed NF- κ B/MAPK activation and attenuated the mitochondrial fission possibly via regulating the nucleus translocation of NRF2, a pivotal transcription factor on redox homeostasis. Our in vivo studies showed that the sh-ZBTB20 adenovirus injection could reduce the progression of AS in apolipoprotein E-deficient (ApoE -/- ) mice. All in all, these results suggested that ZBTB20 positively regulated the oxidative stress level, mitochondrial fission, and inflammatory responses of macrophages induced by ox-LDL, and the knockdown of ZBTB20 could attenuate the development of AS in ApoE -/- mice.